2022
DOI: 10.3390/ma15217643
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Titanium-Base Abutment Height on Optical Properties of Monolithic Anterior Zirconia Crowns

Abstract: The effects of different heights of ti-base abutments on the color of anterior screw-retained zirconia restorations fabricated using computer-aided design and computer-aided manufacturing (CAD-CAM) technologies may affect the optical clinical outcome. The purpose of this study was to measure and compare the color parameters of zirconia crowns in different shades on ti-base abutments. Identical specimens (N = 160) were milled to restore the screw-retained central maxillary incisor crown, using 5% mol yttria zir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Biadsee et al investigated the effect of Titanium-Base Abutment Height revealed that using a 5.5 mm-height ti-base abutment might produce clinically unacceptable color outcomes in certain zirconia crown shades. This finding is crucial for achieving the desired aesthetic results in anterior screw-retained zirconia restorations [94].…”
Section: Adhesion Features Of Translucent Zirconiamentioning
confidence: 93%
“…Biadsee et al investigated the effect of Titanium-Base Abutment Height revealed that using a 5.5 mm-height ti-base abutment might produce clinically unacceptable color outcomes in certain zirconia crown shades. This finding is crucial for achieving the desired aesthetic results in anterior screw-retained zirconia restorations [94].…”
Section: Adhesion Features Of Translucent Zirconiamentioning
confidence: 93%
“…Therefore, a careful selection of the abutment combined with a proper loading protocol is strongly recommended to reduce the effect of forces on the implant system [22]. Although abutment height may have an influence on superstructure retention, light scattering, and restoration translucency and aesthetics, limited data are available investigating its influence on fatigue [23].…”
Section: Introductionmentioning
confidence: 99%